2020
DOI: 10.1038/s41598-020-74211-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression by miRNA-455-3p, upregulated in the conjunctival epithelium of patients with Stevens–Johnson syndrome in the chronic stage

Abstract: To investigate the role of miRNA in the pathogenesis underlying ocular surface complications in patients with Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) in the chronic stage. Using oligonucleotide microarrays, we performed comprehensive miRNA analysis of the conjunctival epithelium of SJS/TEN patients with severe ocular complications (SOC) in the chronic stage (n = 3). Conjunctival epithelium of patients with conjunctival chalasis (n = 3) served as the control. We confirmed the down- and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Affymetrix GeneChip miRNA 4.0 arrays were used for miRNA profiling. Total RNA was labeled with the FlashTag ™ Biotin HSR RNA labeling kit (Affymetrix, Inc., USA) (Ueta et al, 2020;Ueta et al, 2021a). The samples were hybridized on GeneChip miRNA 4.0 arrays (Affymetrix) for 18 h at 48 °C.…”
Section: Microarray Profiling Of Mirnasmentioning
confidence: 99%
“…Affymetrix GeneChip miRNA 4.0 arrays were used for miRNA profiling. Total RNA was labeled with the FlashTag ™ Biotin HSR RNA labeling kit (Affymetrix, Inc., USA) (Ueta et al, 2020;Ueta et al, 2021a). The samples were hybridized on GeneChip miRNA 4.0 arrays (Affymetrix) for 18 h at 48 °C.…”
Section: Microarray Profiling Of Mirnasmentioning
confidence: 99%
“…The expression of miR-18a-5p, miR-124 and miR-375-3p were up-regulated in various cells and body fluids [68][69][70]. Ueta et al (2020) investigated the role of miRNAs in the pathogenesis of SJS/TEN patients with SOC. The expression of miR-31 and miR-455-3p is shown to be significantly up-regulated in the conjunctival epithelium of SJS/TEN chronic patients.…”
Section: F) Steven-johnson Syndromementioning
confidence: 99%
“…The expression of miR-31 and miR-455-3p is shown to be significantly upregulated in the conjunctival epithelium of SJS/ TEN chronic patients. It was further reported that the miR-455-3p regulates many innate immune related genes in human conjunctival epithelium [ 50 ].…”
Section: Role Of Mirnas In the Conjunctival Disordersmentioning
confidence: 99%
“…Indeed, reducing Ankrd1 protein levels has been demonstrated to prevent development of dilated cardiomyopathy in mice (Lange et al 2016 ). A recent study found that Ankrd1 mRNA levels could be downregulated by inhibiting miR-455-3p (Ueta et al 2020 ), a miRNA that was linked to worsened hypertrophic remodeling in mice that underwent pressure overload by transverse aortic constriction (TAC) (Wu et al 2015 ). However, it is unclear if the mouse version of miR-455 targets Ankrd1 mRNA, as the sequences show poor evolutionary conservation between mice and humans.…”
Section: The Emerging Therapeutic Potential Of Modulating Titin I-band Splicing and Phosphorylation As Well As Titin-associated Proteinsmentioning
confidence: 99%